Pengembangan Media Flipbook Berbasis Augmented Reality Materi Keragaman Budaya Untuk Meningkatkan Self Efficacy Siswa Kelas IV - Mufidatul Khusna; Mohamad Fatih; Cindya Alfi (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2024)
Self-efficacy is the ability of students to believe in their abilities. One way to improve students' self-efficacy skills at school is to use instructional media. One of the learning media that can be developed is augmented reality-based flipbook media in IPAS matter. The media was developed with the ADDIE development model. Interviews and questionnaires are data collection techniques used by researchers. Validation from media experts got a score of 87%, material experts got a score of 100% and language experts got a score of 82%. This means that the media developed by the researcher is included in the valid category and can be used for research. the results of increasing students' self-efficacy abilities after learning using flipbook media based on augmented reality are calculated using the N-Gain formula and get a score of 0.5122. These results are included in the moderate category. Thus, it can be concluded that the use of flipbook media can help increase students' self-efficacy and make learning more interesting than previous learning.